2023
DOI: 10.1021/acs.joc.2c02613
|View full text |Cite
|
Sign up to set email alerts
|

Formic Acid as Carbon Monoxide Source in the Palladium-Catalyzed N-Heterocyclization of o-Nitrostyrenes to Indoles

Abstract: The reductive cyclization reaction of o-nitrostyrenes to generate indoles has been investigated for three decades using CO as a cheap reducing agent, but it remains an interesting area of research and improvements. However, using toxic CO gas has several drawbacks. As a result, it is highly preferable to use safe and efficient surrogates for in situ generation of CO from nontoxic and affordable sources. Among several CO sources that have been previously explored for the generation of gaseous CO, here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Both increasing and decreasing the reaction temperature with respect to 140 °C afforded worse results. Finally, we also tested the use of Pd(acac) 2 as catalyst because the use of this complex in acetone as the solvent had given the best results when the HCOOH/Ac 2 O mixture had been employed for the reductive cyclization of o ‐nitrostyrenes to indoles, [19] but neither when employing the conditions optimized in this work nor when using those optimized for the synthesis of indoles afforded improved yields. In the end, the best yield, 77 %, was obtained by working under the conditions of run 10 in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both increasing and decreasing the reaction temperature with respect to 140 °C afforded worse results. Finally, we also tested the use of Pd(acac) 2 as catalyst because the use of this complex in acetone as the solvent had given the best results when the HCOOH/Ac 2 O mixture had been employed for the reductive cyclization of o ‐nitrostyrenes to indoles, [19] but neither when employing the conditions optimized in this work nor when using those optimized for the synthesis of indoles afforded improved yields. In the end, the best yield, 77 %, was obtained by working under the conditions of run 10 in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, Mo(CO) 6 , [15] Co 2 (CO) 8 , [16] and benzenetriformate [17] have also been employed as CO surrogates in the field of the synthesis of N ‐heterocycles by reduction of nitroarenes, but they also produce stoichiometric byproducts whose separation may complicate the work‐up. To solve this problem, we recently developed the use of the formic acid/acetic anhydride mixture [18] to prepare indoles from o ‐nitrostyrenes [19] and 4‐quinolones from 2′‐nitrochalcones [20] . The use of this mixture, from which the mixed anhydride is generated in situ , not only avoids the coproduction of phenol but also saves a synthetic step and improves the atom economy of the full process because phenyl formate is itself prepared by the reaction of phenol with an excess of HCOOH/Ac 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using toxic CO gas, the authors made use of low‐cost and easily available formic acid 9 as an efficient alternative for in situ generation of CO that works as a potent reductant to carry out the reductive cyclization of o‐nitrostyrenes 8 (Scheme 3). [24] The use of low Pd catalyst loading (0.5 mol %) and air and water tolerance of the reaction minimizes the formation of by‐products, providing the desired indoles in excellent yields. The authors have scaled up the reaction to 2 g which demonstrated the applicability of the developed strategy for industrial purposes.…”
Section: Metal‐catalysed Synthesis Of Indolesmentioning
confidence: 99%
“…All these facts result in a huge demand for efficient approaches towards amide bond formation in the pharmaceutical industry. 5–13…”
mentioning
confidence: 99%
“…All these facts result in a huge demand for efficient approaches towards amide bond formation in the pharmaceutical industry. [5][6][7][8][9][10][11][12][13] One of the possible ways to overcome these problems is using nitroarenes as a nitrogen source and coupling them with carboxylic acids without activators. Nitroarenes are stable and cheap reagents.…”
mentioning
confidence: 99%